2021
DOI: 10.3390/ijerph182312675
|View full text |Cite
|
Sign up to set email alerts
|

The Digital Divide and Active Aging in China

Abstract: With the rapid development of society, especially the advent of intelligent technology of life services, the ability of the elderly to adapt to modern digital life is getting weaker and weaker, the dilemma of the “digital divide” for the elderly has aroused heated public debate. In the era of aging and information superposition, in-depth study of the multi-dimensional impact of the digital divide on the elderly has become an effective content of China’s active aging strategy. Based on the micro-data of the Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 17 publications
1
32
0
1
Order By: Relevance
“…A recent survey [31] that focused on the user ability of a more educated cohort (94% Ph.D. or Master's degree; 6% Bachelor's degree or undergraduate) in 28 countries worldwide showed that even this group had serious concerns regarding the utility, safety, accessibility, and efficiency of "smart" services. The digital divide, particularly in the Global South and for the elderly, is of concern [32][33][34][35][36] and must be considered using an inclusionary and participatory approach [37][38][39]. It seems, then, that community consultation (or participatory planning, or what we term here "familiarity" with community) should be incorporated as an important element of Smart City planning (or the bottom-up approach, as noted above), with Allahar [24] concluding that "The success of building smart cities has been traced by some scholars to depth of community engagement and level of citizen participation".…”
Section: What Is a Smart City?mentioning
confidence: 99%
“…A recent survey [31] that focused on the user ability of a more educated cohort (94% Ph.D. or Master's degree; 6% Bachelor's degree or undergraduate) in 28 countries worldwide showed that even this group had serious concerns regarding the utility, safety, accessibility, and efficiency of "smart" services. The digital divide, particularly in the Global South and for the elderly, is of concern [32][33][34][35][36] and must be considered using an inclusionary and participatory approach [37][38][39]. It seems, then, that community consultation (or participatory planning, or what we term here "familiarity" with community) should be incorporated as an important element of Smart City planning (or the bottom-up approach, as noted above), with Allahar [24] concluding that "The success of building smart cities has been traced by some scholars to depth of community engagement and level of citizen participation".…”
Section: What Is a Smart City?mentioning
confidence: 99%
“…Furthermore, older adults, as the recipients of OAE, are not fully aware of the concept of “lifelong learning” and the importance of participating in OAE; they do not realize the vital role of OAE in improving health literacy, relieving anxiety, and benefiting their own development (particularly their social development). Finally, despite the global digitalization process, older adults have a limited acceptance of information and network technologies, applications, and innovation capabilities; the existence of a “digital divide” hinders active aging ( 30 ).…”
Section: Challenges Of Oaementioning
confidence: 99%
“…The demands of older people for intelligent aging products (e.g., smart bracelets, smartwatches, smart crutches, and smart call badges) are increasing [ 44 ]. However, older adults’ ability to adapt to modern digital life is weak, and many of them cannot access the Internet, download APPs, or obtain the required information digitally, which means older people cannot enjoy the convenience brought by digital and intelligent services [ 6 , 7 , 8 , 16 ]. According to the Chinese National Bureau of Statistics, 13.5% of China’s population was over 65 in 2020.…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%
“…Furthermore, the daily lives of Chinese people are increasingly dependent on technology. Due to poor adaptability to technology, older adults are facing difficulties in using digital products and platforms [ 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%